2009
DOI: 10.4314/sajas.v39i1.43550
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the 5’-flanking region of the prolactin gene and the association with reproduction traits in geese (Short communication)

Abstract: Prolactin (PRL), a polypeptide hormone synthesized and secreted by the animal's anterior pituitary gland, plays an important role in the regulation of mammalian lactation and avian reproduction. Considering the significant association between single nucleotide polymorphisms (SNPs) in the 5'-flanking region of PRL and reproduction traits in the chicken, the objective of this study was to screen for SNP in the 5'-proximal region of PRL in geese and to evaluate the association between SNP and reproduction traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In ducks it has been shown that post hatching parental care is regulated by high levels of prolactin (Boos et al 2007), which in turn seems to have a genetic basis in geese (Jiang et al 2009). Future common garden experiments could elucidate whether this change in parental care is caused by phenotypic plasticity or evolution.…”
Section: Discussionmentioning
confidence: 98%
“…In ducks it has been shown that post hatching parental care is regulated by high levels of prolactin (Boos et al 2007), which in turn seems to have a genetic basis in geese (Jiang et al 2009). Future common garden experiments could elucidate whether this change in parental care is caused by phenotypic plasticity or evolution.…”
Section: Discussionmentioning
confidence: 98%
“…P rolactin (PRL) is one of the hormone family that includes growth hormone (GH), placental lactogen (PL), and somatolactin (Power, 2005). It is a polypeptide hormone which synthesized and secreted by the animal's anterior pituitary gland (Jiang et al, 2009) and playing an essential role in regulating reproduction and lactation in mammals (Bonomo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Three mutations screened (C-1607T, C-5749T and T-5821C) by Liu et al (2007) showed that there is a correlation between different haplotypes and egg production. In geese, three SNPs (A-401G, G-268A and T-266A) in the 5'-proximal region of PRL gene have been screened and statistical analysis suggested that these polymorphisms have the potential to be utilized in molecular breeding for egg production (Jiang et al, 2009). All the above studies displayed that PRL is an important candidate gene on egg production.…”
Section: Introductionmentioning
confidence: 99%